Identificação de potenciais plantas hospedeiras do complexo de vírus da meleira do mamoeiro (PMeV e PMeV2) - Hell, Marcos Vinicius (2021)
The papaya culture (Carica papaya L.) has an expressive participation in the national fruit production, being the third most consumed fruit in the country. One of the main diseases that affects papaya plantations in Brazil is the papaya sticky disease, caused by the viral complex papaya meleira virus (PMeV) and papaya meleira virus 2 (PMeV2). Until then, the best strategy available to control the disease is to eradicate infected plants. However, it is believed that the virus is able to remain in secondary species, such as invasive and intercropped plants. The identification of model host plants of the PMeV complex aims to provide advances in the study of virus-plant interaction. Thus, the objective of this work was to identify host plants of the viral complex. Eight species of plants (Citrullus lanatus, Cucurbita moschata, Nicotiana benthamiana, Nicotiana tabacum, Phaseolus vulgaris, Vigna unguiculata, Momordica charantia and Carica papaya) were inoculated, mechanically, by abrasive action and injection in the stem apex, with inoculum obtained from latex of infected papaya plants, with four replications. Additionally, in C. papaya, the inoculation was also performed with the leaf cut. Samples were collected before inoculation and at 15, 30 and 45 days after inoculation for indexing by RT-PCR. At 15, 30 and 45 days after inoculation, a visual assessment of the plants was performed, for local and systemic symptoms. The species C. lanatus, C. moschata and N. benthamiana were positive for the presence of PMeV and PMeV2 in the RT-PCR reaction. At 30 days, the plants of C. lanatus and C. moschata showed lesions in the leaf margin and N. benthamiana exhibited symptoms of chlorosis between the veins. There was no difference between the inoculation methods in the plants of C. papaya. This is the first time that host plants for the PMeV and PMeV2 viruses have been confirmed, which enables new possibilities for investigating the plant virus interaction under controlled conditions and establishing new disease management strategies.